Integration of Healthy Eating Habits and Physical Activity through Nutrition Care Process to Tackle the Obesity Epidemic: A Narrative Review of the Evidence - Philippou, Christiana; Andreou, Eleni (Arab Journal of Nutrition and Exercise (AJNE), 2022)
Background: Obesity is a rising global health problem which is already at epidemic proportions. Effective methods of treatment are required and should be imparted by efficient means to dietitians and other health professionals dealing with weight management. Research shows that behavioral modification techniques are the most effective way to achieve and maintain a healthy weight compared to diet and physical activity alone. Aim: This narrative review focusses on diet and physical activity behavioral modification techniques to promote effective weight management for sedentary and active adults using the Nutrition Care Process (NCP). Methods: PubMed, Scopus, Embase, Science Direct, Web of Science and Pro-Quest databases were searched for relevant articles. Results: A healthy eating habit is one of the contributing factors to improved health. Physical activities also help improve and maintain one’s health. This article discusses the importance of eating habits and physical activities among school students. In addition, health issues related to eating habits and the practice of physical activities are also highlighted. Overall, the results revealed that healthy eating habits and regular physical activities help in maintaining good health. Conclusion: NCP is a systematic approach to provide high-quality nutrition care. Using the NCP does not mean that all clients get the same care. Use of a care process provides a framework for the dietitian to individualize care, taking into account clients’ needs and values, and using the best evidence available to make decisions. Keywords: obesity, weight control, physical activity, nutrition knowledge, eating habits, nutrition care process